2021
DOI: 10.1097/md.0000000000023926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on blood coagulation and C-reactive protein level among children with mycoplasma pneumoniae pneumonia by different chest imaging findings

Abstract: Mycoplasma pneumoniae infection may induce a systemic hypercoagulable abnormality, like organ embolism and infarction. Indexes of blood coagulation and C-reactive protein (CRP) have been reported different between healthy people and mycoplasma pneumoniae pneumonia (MPP) patients, but this difference in MPP patients with different chest imaging findings has rarely been reported. We performed a retrospective study of 101 children with MPP and 119 controls, combined with radiological examination and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…VitA is also an important regulatory factor for cell differentiation and proliferation. During mycoplasma infection, VitA may promote repair and recovery by regulating the proliferation and differentiation of damaged lung tissue cells, which helps to accelerate the disappearance of lung rales and alleviate coughing and fever ( 21 ). Although the role of VitA in the immune system and respiratory infections has been preliminarily confirmed, the specific treatment effect still needs to consider the impact of individual differences on the efficacy of VitA.…”
Section: Discussionmentioning
confidence: 99%
“…VitA is also an important regulatory factor for cell differentiation and proliferation. During mycoplasma infection, VitA may promote repair and recovery by regulating the proliferation and differentiation of damaged lung tissue cells, which helps to accelerate the disappearance of lung rales and alleviate coughing and fever ( 21 ). Although the role of VitA in the immune system and respiratory infections has been preliminarily confirmed, the specific treatment effect still needs to consider the impact of individual differences on the efficacy of VitA.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory tests showed that co-infections caused an increase in D-dimer and fibrinogen values, causing a higher risk of thrombosis. MP and CP are bacteria known to evoke hypercoagulability [18,19]. Furthermore, co-infections increase the risk of thrombosis compared to patients with COVID-19 infection alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, co-infections increase the risk of thrombosis compared to patients with COVID-19 infection alone. The D-dimer assessment is strongly recommended in routine anticoagulant prophylaxis [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…How to make clear the early diagnosis of MPP and accurately assess its severity is the focus of current pediatric research. It is widely believed that MP proliferates in respiratory epithelial cells by binding P1 protein to cilia, stimulates the production of pro‐inflammatory cytokines in airway mucosa, induces cellular inflammatory response and tissue damage and ultimately leads to changes in host immune function 5,6 . The imbalance of Th1/Th2 function after M. pneumoniae infection is an important immunological mechanism of MPP.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that MP proliferates in respiratory epithelial cells by binding P1 protein to cilia, stimulates the production of pro‐inflammatory cytokines in airway mucosa, induces cellular inflammatory response and tissue damage and ultimately leads to changes in host immune function. 5 , 6 The imbalance of Th1/Th2 function after M. pneumoniae infection is an important immunological mechanism of MPP. Therefore, it is important to study the results of serum inflammatory cytokines in children with MPP for guiding clinical treatment.…”
Section: Introductionmentioning
confidence: 99%